2014
DOI: 10.1103/physrevd.90.023529
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological model with variable vacuum pressure

Abstract: Scenarios of the cosmological evolution are studied by using an equation of state (EoS) having points where the specific enthalpy of the cosmological fluid vanishes. A large class of barotropic EoS's admits, depending upon initial conditions, analogues of the "Big Rip", as well as solutions describing exponential inflation followed by usual matter dominance; their classification is proposed. We discuss extensions to more general two-parametric EoS dealing with a pre-inflationary evolution and yielding stages w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Combining this energy definition with the thermodynamic pressure definition and the Friedmann second equation, we got the p(V ) relation. Bearing the Friedmann first equation in mind, we could obtain the p(ρ) relation, and showed that the obtained solutions can be used to model the universe expansion, a result which is in agreement with some previous attempts [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. We also found out that some type of the obtained solutions may be used to unify the dominated fluids in both the primary inflationary and current accelerating phases into one model.…”
Section: Summary and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Combining this energy definition with the thermodynamic pressure definition and the Friedmann second equation, we got the p(V ) relation. Bearing the Friedmann first equation in mind, we could obtain the p(ρ) relation, and showed that the obtained solutions can be used to model the universe expansion, a result which is in agreement with some previous attempts [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. We also found out that some type of the obtained solutions may be used to unify the dominated fluids in both the primary inflationary and current accelerating phases into one model.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…Let us compare our results with those of Ref. [22] a little more. Comparing their result (µ > 0) with Eq.…”
Section: The General Proposal For Energy and Its Consequencesmentioning
confidence: 56%
See 1 more Smart Citation
“…There are various attempts to give a candidate for describing DE and solving the standard cosmology problems [12][13][14]. Among these attempts, some models include a varying DE candidate with equation of state P = ρ + f (ρ), where P and ρ are the DE pressure and energy density, respectively [15,16]. In astrophysics, a Polytropic gas with equation of state…”
Section: Introductionmentioning
confidence: 99%
“…Але досить часто на перший план виходять якісні властивості космологічних сценаріїв, а саме: чи існує розв'язок для усіх часів, почи-наючи від космологічної сингулярності або він означений на скінченному інтервалі, коли прямують до нескінченності густина енергії або тиск і за яких умов тощо (див., напр., огляди в [5][6][7][8]). З цією метою в [8] було досліджено якісну поведінку розв'язків в гідродинамічній моделі однорідного ізотропного Всесвіту; баротропне рівняння стану, що роз-глядалося, було досить загальним, тим не менш, були застосовані певні обмеження щодо монотонності деяких складових цього рівняння. У даній роботі ми знімаємо ці обмеження і розглядаємо баротропне рівняння стану = ( ) p p e , яке пов'язує тиск p та інваріантну густину енергії e космологічної рідини лише за загальних умов одно-значності та гладкості.…”
unclassified